Servant Leadership, Motivasi Kerja, Kinerja Karyawan Dan Komitmen Organisasi - Nelly F.M.L Dumatubun (Universitas Musamus,Merauke,Papua, 2021)
This scientific study is dedicated to the Department of Education and Teaching (P&P) of Mappi-Papua Regency which is expected to be able to contribute to improving the performance of employees at the agency. Reviewing Servant leadership, Work motivation, Employee performance and Organizational commitment with regression analysis as a test tool. The results show. Servant leadership has an impact on work motivation by 35.1% with a positive coefficient of 0.563. Where the leader needs to pay attention to the support of facilities and infrastructure in supporting the work process, as well as good relations and communication within the agency. Servant leadership has an impact on work performance by 42.6% and a positive coefficient value of 0.527. Leaders need to place human resources in the field of work in accordance with the knowledge and abilities of these human resources, determine work achievement targets according to the type of work, prioritize work that is urgent in accordance with the situation and needs, both needs within the agency and the public service, reports the results of activities, evaluate and see the sustainability of the program of activities that have been carried out, and it is necessary to pay attention to time discipline (hours for office/going home). Servant leadership has an impact on organizational commitment by 47.3% and a positive coefficient value of 0.473. Leaders need to form a work team and empower, and give confidence to all staff in carrying out their duties and responsibilities. Fair treatment needs to be considered in the agency, both in terms of assigning tasks and giving sanctions to violates agency rules.